International Energy Security Indicators and Turkey’s Energy Security Risk Score - Kocaslan, Gelengul (International Journal of Energy Economics and Policy, 2014)
Energy security has been a priority for many countries. What makes energy security that important is; its bilateral relationship with economic, political, social, environmental sustainability and military issues. As an inevitable consequence of globalization cooperation in the field has been a must and it is required international energy security indicators to make energy security risk evaluations in order to establish adequate policies. The aim of the study is to review energy security within the concept of international energy security indicators, international energy security risk index, international energy security rankings and to reveal Turkey’s energy security risk summary emphasizing the components of energy security issue. Keywords: Energy security indicators; energy security risk. JEL Classifications: F50; Q40.